2021
DOI: 10.3174/ajnr.a7134
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Venous Thrombosis in COVID-19: A New York Metropolitan Cohort Study

Abstract: BACKGROUND AND PURPOSE: Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) infection is associated with hypercoagulability. We sought to evaluate the demographic and clinical characteristics of cerebral venous thrombosis among patients hospitalized for coronavirus disease 2019 (COVID-19) at 6 tertiary care centers in the New York City metropolitan area. MATERIALS AND METHODS:We conducted a retrospective multicenter cohort study of 13,500 consecutive patients with COVID-19 who were hospitalized betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 50 publications
0
61
0
2
Order By: Relevance
“…The question remains nevertheless as to whether any such processes bear similarity in whole or part to thromboses that are otherwise found during active COVID-19 infections. In particular and with special reference to cerebral thrombosis, retrospective study suggests that COVID-19 in itself attracts an incidence of the latter which exceeds that expected in the general uninfected population [114,139].…”
Section: Thrombotic Events and Covid-19 Vaccinationmentioning
confidence: 95%
“…The question remains nevertheless as to whether any such processes bear similarity in whole or part to thromboses that are otherwise found during active COVID-19 infections. In particular and with special reference to cerebral thrombosis, retrospective study suggests that COVID-19 in itself attracts an incidence of the latter which exceeds that expected in the general uninfected population [114,139].…”
Section: Thrombotic Events and Covid-19 Vaccinationmentioning
confidence: 95%
“…Therefore, the possibility of this potentially life-threatening condition should not be overlooked even when patients present several days to weeks after the onset of COVID-19. A more recent multicenter 3-month cohort study of 13,500 consecutive patients with COVID-19 in New York City found an imaging-proved cerebral venous thrombosis incidence of 8.8 per 10,000 cases, which is higher than expected (i.e., 5 per million annually) [ 88 ]. In this study, despite the standard management [ 89 ] consisting of anticoagulation, endovascular thrombectomy and surgical hematoma evacuation, the mortality rate was 25% [ 88 ].…”
Section: Acute Cerebrovascular Events In Covid-19mentioning
confidence: 99%
“…In vereinzelten Fällen wurden auch Sinusvenenthrombosen im Rahmen einer COVID-19-Erkrankung erfasst [ 2 ]. Patienten mit zerebrovaskulären Erkrankungen in der Anamnese sowie auch zerebrovaskulären Komplikationen im Verlauf einer COVID-19-Erkrankungen haben ein höheres Risiko für einen schwereren Verlauf (Chou S et al.…”
Section: Erkrankungen Des Zentralen Nervensystemsunclassified